Open Reduction and Internal Fixation of Volar Barton Fracture: A Clinical Study - Afzaal Rafeeq Ansari; Ashok Rawat; Utsav Aman (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: A Barton’s fracture is a compression injury with a marginal shearing fracture of the distal radius. The management of volar Barton’s fractures either by operative or conservative means is a difficult problem. The objective of the study is to assess the functional and clinical outcome of open reduction and internal fixation (ORIF) by buttress T-plate in the treatment of volar Barton’s fracture of the wrist. Materials and Methods: Between March 2019 and January 2022, a total of 20 cases of volar Barton’s fracture were operated at Prasad Institute of Medical Sciences, Lucknow. Henry’s approach was used to open the fractures and AO system was used to classify the fractures. The cause of injury was road traffic crash in 15 cases and fall in 5. All cases were type B3 with 10 B3.3, 5 B3.2, and 5 B3.1 subtypes. All cases underwent surgery within the 1st week of injury. Results: All cases were assessed clinically and radiographically after a mean follow-up duration of 18 months (range 6–36 months). Fracture healed after 7–10 weeks (mean 8.8 weeks). Based on Mayo’s Wrist Score criteria, the results were excellent in 12 cases, good in 6, and fair in 2. Mild osteoarthritis developed secondary to trauma in one case. There was no neurovascular deficit in any of 20 cases. Conclusion: ORIF of volar Barton’s fracture with buttress T-plate can restore articular congruity and stability to achieve good results.